2019
DOI: 10.5194/acp-19-3191-2019
|View full text |Cite
|
Sign up to set email alerts
|

Organosulfates in Atlanta, Georgia: anthropogenic influences on biogenic secondary organic aerosol formation

Abstract: Abstract. Organosulfates are secondary organic aerosol (SOA) products that form from reactions of volatile organic compounds (VOC), such as isoprene, in the presence of sulfate that is primarily emitted by fossil fuel combustion. This study examines the anthropogenic influence on biogenic organosulfate formation at an urban site in Atlanta, Georgia (GA) in the southeastern United States (US). Organosulfates were analyzed in fine particulate matter (PM2.5) collected during August 2015 in Atlanta using hydrophil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
148
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(167 citation statements)
references
References 62 publications
15
148
4
Order By: Relevance
“…Remarkably, at both sites, the concentrations of single and total MT-OSs were considerably lower than previously reported for isoprene-derived OS in urban summertime PM 2.5 from the south-eastern United States. As described by Hettiyadura et al (2019), an average concentration of 1792 ng m À3 was determined for methyltetrol sulfate, which accounted for 12.6 % of PM 2.5 OC alone. Other isoprene-derived OSs showed significantly lower concentrations of 1-131 ng m À3 , which were still larger than most of the MT-OS concentrations determined for MEL and NCP.…”
Section: Quantification Of Terpenoid Ossmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, at both sites, the concentrations of single and total MT-OSs were considerably lower than previously reported for isoprene-derived OS in urban summertime PM 2.5 from the south-eastern United States. As described by Hettiyadura et al (2019), an average concentration of 1792 ng m À3 was determined for methyltetrol sulfate, which accounted for 12.6 % of PM 2.5 OC alone. Other isoprene-derived OSs showed significantly lower concentrations of 1-131 ng m À3 , which were still larger than most of the MT-OS concentrations determined for MEL and NCP.…”
Section: Quantification Of Terpenoid Ossmentioning
confidence: 99%
“…Nonetheless, more recent studies have shown that, in particular, the application of new developments in separation techniques, such as hydrophilic interaction LC (also referred to as HILIC), can substantially increase the number of detectable isoprene OS and facilitate their identification and quantification (Cui et al 2018;Hettiyadura et al 2015Hettiyadura et al , 2017Hettiyadura et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of OSs in aerosol samples has been performed by using various measurement techniques, including liquid chromatography (LC) (also including hydrophilic interaction LC) mass spectrometry (MS) (Cui et al, 2018; Hettiyadura et al, 2017; Hettiyadura et al, 2019; Stone et al, 2012), single particle MS (Hatch et al, 2011), particle analysis laser mass spectrometer (Liao et al, 2015), Raman microspectroscopy (Bondy et al, 2018), electrospray ionization coupled with ultra‐high‐resolution MS (Lin, Yu, et al, 2012; O'Brien et al, 2014; Tao et al, 2014), and ultra‐high‐performance liquid chromatography (UHPLC) coupled to Orbitrap MS (Huang, Cochran, et al, 2018; Wang et al, 2016; Wang, Zhang, et al, 2019). However, due to a lack of authentic standards, quantification of OSs is still challenging, which results in studies on OSs largely remaining at the qualitative level (O'Brien et al, 2014; Tao et al, 2014; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Semiquantification methods in some research showed that OSs accounted for 4–30% of organic matter (OM) (Hawkins et al, 2010; Surratt et al, 2008; Tolocka & Turpin, 2012) and 4–14% of total sulfate (Lukacs et al, 2009; Stone et al, 2012) in fine particles. Most previous work regarding OSs were examined in Europe (Frossard et al, 2011; Iinuma et al, 2007; Kristensen & Glasius, 2011; Lukacs et al, 2009; Nguyen et al, 2014) and the United States (Glasius, Bering, et al, 2018; Hettiyadura et al, 2019; Hughes & Stone, 2019; Olson et al, 2011; Riva et al, 2015; Riva et al, 2019; Tolocka & Turpin, 2012), but only a few studies were conducted in Asia (Huang, Cao, et al, 2018; Ma et al, 2014; Stone et al, 2012; Wang, Ma, et al, 2019), especially in China.…”
Section: Introductionmentioning
confidence: 99%
“…from diverse environmental sources have been reported to act as precursors of organic aerosols (Hallquist et al, 2009;Tao et al, 2017;Volkamer et al, 2009;Carlton et al, 2009;Ziemann and Atkinson, 2012;Gentner et al, 2017;Hettiyadura et al, 2019;Majdi et al, 2019;Lim et al, 2019;Maclean et al, 2017). Numerical simulations have been carried out at the molecular level to gain insights into the morphology of aerosols and the energetics of their nucleation from VOCs (Chakraborty and Zachariah, 2011;Li et al, 2010;Ma et al, 2011;Zhao et al, 2019;Hede et al, 2011).…”
mentioning
confidence: 99%